Land surface dynamics: A Multiphysics Approach to Modeling Mass Transport - Aditya Sahu (International Journal of Land, 2025)
Land surface dynamics are governed by complex interactions among hydrological, atmospheric, and geomorphological processes that collectively drive the transport of mass across terrestrial environments. Traditional modeling approaches often isolate individual mechanisms, limiting their ability to capture the coupled feedbacks that shape landscape evolution. This study presents a multiphysics framework for modeling mass transport on land surfaces, integrating fluid flow, sediment transport, heat exchange, and chemical reactions within a unified computational system.The approach leverages coupled partial differential equations to represent the interplay between surface water flow, subsurface infiltration, erosion–deposition cycles, and contaminant migration. Advanced numerical methods, including finite element and finite volume schemes, are employed to resolve nonlinearities and heterogeneities across scales ranging from soil aggregates to watershed basins.Results demonstrate that the multiphysics model can reproduce emergent phenomena such as channel formation, slope instability, and pollutant dispersion under varying climatic and anthropogenic conditions. By bridging hydrology, geomorphology, and environmental engineering, this framework provides a robust tool for predicting land surface responses to extreme events, land-use change, and climate variability. Ultimately, the study underscores the importance of integrated modeling in advancing sustainable land management and hazard mitigation strategies, offering new insights into the coupled dynamics that govern Earth’s surface systems.
Keywords: Geomorphological; Integrated modeling; coupled partial differential equations